Advances to Electrode Pullback in Cochlear Implant Surgery - Ingo Todt; Dietmar Basta; Rainer Seidl; Arne Ernst (The Scientific World Journal)
Objective. To observe the intracochlear behavior of a cochlear implant electrode insertion technique (called “pullback”) in temporal bones. Study Design. Experimental. Settings. Tertiary referral center. Method. The change of the intracochlear electrode position was investigated under various conditions of an electrode pullback (N=54) in 9 radiologically, size-estimated temporal bones (TBs). Those TBs were prepared by removal of the cochlear scalar roof to apply digital video capture procedures to monitor the pullback procedures. The digitally captured pictures were analyzed with specific software. Results. An optimal pullback of the electrode varied between 1.37 mm and 2.67 mm. While a limited pullback is without risk, an extended pullback bears the risk of removing the electrode tip out of its initial position or out of the cochlea. A correlation between cochlear size and the amount of pullback was not found. Conclusion. An initial insertion to the first or the second marker on the electrode followed by a limited pullback of about 1.37 mm to 1.5 mm can be recommended to achieve an optimized perimodiolar position. A pullback of up to two marker positions bears the risk of removing the electrode tip out of its initial position.